2020
DOI: 10.1101/2020.04.12.20059618
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 outbreak at a large homeless shelter in Boston: Implications for universal testing

Abstract: The circumstances of homelessness create the potential for rapid transmission of SARS-CoV-2 in this vulnerable population. Upon observing a cluster of COVID-19 cases from a single large homeless shelter in Boston, Boston Health Care for the Homeless Program conducted symptom assessments and polymerase chain reaction (PCR) testing for SARS-CoV-2 among all guests residing at the shelter over a 2-day period. Of 408 participants, 147 (36.0%) were PCR-positive for SARS-CoV-2. COVID-positive individuals were more li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
2
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 0 publications
1
43
2
1
Order By: Relevance
“…Another study conducted in a homeless shelter in Boston, MA, USA, confirmed that standard COVID-19 symptoms like cough, shortness of breath, and fever were uncommon among individuals who tested positive and strongly argues for universal PCR testing on that basis. 71 Also, besides enhancing the tests of mild/asymptomatic cases, some disease control centers, such as the ECDC, recommend that group testing should potentially be applied to prevalence studies. 72 The pooling schemes suggested here can also include routine tests of cohesive subpopulations with high prevalence, such as health care workers, and therefore propose a sensible way to include commonly available information about risk group into the setup.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study conducted in a homeless shelter in Boston, MA, USA, confirmed that standard COVID-19 symptoms like cough, shortness of breath, and fever were uncommon among individuals who tested positive and strongly argues for universal PCR testing on that basis. 71 Also, besides enhancing the tests of mild/asymptomatic cases, some disease control centers, such as the ECDC, recommend that group testing should potentially be applied to prevalence studies. 72 The pooling schemes suggested here can also include routine tests of cohesive subpopulations with high prevalence, such as health care workers, and therefore propose a sensible way to include commonly available information about risk group into the setup.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of such estimates described above lead to a recent collaborative effort between FIND, a Swiss foundation for diagnostics, and the World Health Organization for the COVID-19 pandemic in order to evaluate the qRT-PCR tests and to assess their accuracy. 42 FIND is currently evaluating a list of more than 300 SARS-CoV-2 tests commercially available and to establish accurate estimates for sensitivity and specificity with their respective confidence intervals. 43 Based on the preliminary findings, in this work we will assume that the specificity of a single PCR test is 99%.…”
mentioning
confidence: 99%
“…2 In a Boston homeless shelter, 100% of 147 COVID-19 positive subjects were asymptomatic. 3 The mechanisms underlying severe COVID-19 should account for both these findings, as well as other COVID-19 mortality risk factors: hypertension, obesity, male sex, advanced age, concentration in northern climates, and COVID-19 associated coagulopathy (CAC). 4,5 Vitamin D insufficiency (VDI) meets every one of the above criteria.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Ferguson et al [34] assumed that 50% of the infected individuals could be asymptomatic. Recent evidence shows the possibility of a greater number of asymptomatic patients [44,45,26,11]. Thus, we created a correction factor to the table described by Verity et al [31] based on the work of Ioannidis et al [22] and adapted it for the relative risk of ICU-level care and death according to age and asymptomatic percentage.…”
Section: Discussionmentioning
confidence: 99%